Transplantation of patient‐specific bile duct bioengineered with chemically reprogrammed and microtopographically differentiated cells - Elina Maria Buisson; Suk‐Hee Park; Myounghoi Kim; Kyojin Kang; Sangtae Yoon; Ji Eun Lee; Young Won Kim; Nak Kyu Lee; Mi Ae Jeong; Bo‐Kyeong Kang; Seung Bum Lee; Valentina M. Factor; et al. (Wiley, 2022)
Abstract Cholangiopathy is a diverse spectrum of chronic progressive bile duct disorders with limited treatment options and dismal outcomes. Scaffold‐ and stem cell‐based tissue engineering technologies hold great promise for reconstructive surgery and tissue repair. Here, we report a combined application of 3D scaffold fabrication and reprogramming of patient‐specific human hepatocytes to produce implantable artificial tissues that imitate the mechanical and biological properties of native bile ducts. The human chemically derived hepatic progenitor cells (hCdHs) were generated using two small molecules A83‐01 and CHIR99021 and seeded inside the tubular scaffold engineered as a synergistic combination of two layers. The inner electrospun fibrous layer was made of nanoscale-macroscale polycaprolactone fibers acting to promote the hCdHs attachment and differentiation, while the outer microporous foam layer served to increase mechanical stability. The two layers of fiber and foam were fused robustly together thus creating coordinated mechanical flexibility to exclude any possible breaking during surgery. The gene expression profiling and histochemical assessment confirmed that hCdHs acquired the biliary epithelial phenotype and filled the entire surface of the fibrous matrix after 2 weeks of growth in the cholangiocyte differentiation medium in vitro. The fabricated construct replaced the macroscopic part of the common bile duct (CBD) and re‐stored the bile flow in a rabbit model of acute CBD injury. Animals that received the acellular scaffolds did not survive after the replacement surgery. Thus, the artificial bile duct constructs populated with patient‐specific hepatic progenitor cells could provide a scalable and compatible platform for treating bile duct diseases.